STUDY ON EARLY PHYSICAL THERAPY IN POSTOPERATIVE INTERVENTION ON CHILDREN WITH MYELOMENINGOCELE - Necula Dana; Marcu Vasile; Pădure Liliana; Hodorcă Raluca Mihaela (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2015)
Objectives targeted in early intervention thru physical therapy postoperative, to recover the functional for the neuro-musculo-arthropod kinetic system and prevent bone deformities and dysfunctions of micturition and defecation sequlae. Materials and methods The study included 12 children aged 0-5 years, 7 boys and 5 girls that followed at least 12 months of recovery. The group included children with hydrocephalus associated with myelomeningocele and equinus foot lime, lime myelomeningocele and equinus foot (with varying degrees of paraplegia mono or bilateral) and children with myelomeningocele and only urinary dysfunction and lower limb hypotonia. Results and discussion: Initial tests showed the presence of lumbar neurological paraplegia disorders with symptoms as urination and defecation dysfunction, impaired neuromotor development as a result of hydrocephalus, mono or bilateral foot equine deviated lime and dysplasia of the hip joint. Conclusions: Early physiotherapy intervention after complex neurosurgical intervention has an important role in regaining muscle tone, joint mobility and muscle strength in the lower body, improving and regaining alignment vault planting. Also we mention prophylaxis of the urinating device and prevention of deficiencies in postural alignment of the spine and pelvis.